Requirements for a successful implementation of drug interaction information systems in general practice: results of a questionnaire survey in Germany - Bergk, Verena; Gasse, Christiane; Schnell, Rainer; Haefeli, Walter E. (European journal of clinical pharmacology, 2004)
Objective: To determine drug interaction information requirements in general practice with respect to both content and mode of presentation. Methods: In a mail survey among 2,000 general practitioners in south-west Germany, we collected information on risk evaluation of drug interactions and combinations of concern, usage of and satisfaction with the current information sources, desirable content and mode of future presentation and demographic variables. Categorical variables were compared using χ2 test. Trends were analysed with Cochran-Armitage test and determinants of literature usage with logistic regression. Results: Response rate was 60.8%. The majority of general practitioners considered drug interactions a risk factor in prescribing (88.6%). For 18.2% of the drug combinations most frequently indicated as interacting, there was no published evidence of a clinically relevant interaction. More than half of the participants were dissatisfied with the information on severity, mechanism, and dose adjustment currently available in their sources. In particular, non-interacting alternatives were thought to be lacking (86.9%). Users of drug interaction software more frequently retrieved drug interaction information than non-users [odds ratio (OR) 1.95; 95% confidence intervals (CI) 1.50, 2.52], but only 28.6% of general practitioners had access to such systems. There was a significant trend towards electronic sources among younger physicians, but at present, 41.7% of general practitioners favour printed sources, and 8.8% would refuse to use electronic sources. Conclusion: General practitioners wish for more informative support on drug interactions, especially concerning management. Despite a trend towards electronic information sources, printed documents are presently still required to reach all prescribers.
Gesehen am 19.05.2021